Pengaruh Net Profit Margin (NPM) dan Debt to Equity Ratio (DER) Terhadap Harga Saham Pada Perusahaan Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Kylla Almira Rahma Fadzillah; Dini Nurhandayani; Fadlillah Ramadhan; Meilani Tri Pratiwi; Alfiana (Indo Publishing, 2025)
The global economy has experienced significant instability due to various factors such as the COVID-19 pandemic, geopolitical conflicts, the exchange rate of the rupiah, Bank Indonesia’s interest rate (BI Rate), rising inflation, and changes in monetary policy. These conditions have directly impacted market performance, marked by stock price fluctuations and increased investment uncertainty. This study aims to analyze the effect of Net Profit Margin (NPM) and Debt to Equity Ratio (DER) on the stock prices of Food and Beverage Sector companies listed on the Indonesia Stock Exchange during the period 2020-2024. The data used in this study are sourced from financial reports published during the specified period. The research method applied is panel data regression analysis to determine the relationship and influence between independent variables (NPM and DER) and the dependent variable (stock price). The results show that NPM has a positive effect on stock prices, indicating that higher NPM reflects better performance and profitability, which can attract investors and cause stock prices to rise. Meanwhile, DER has a negative effect, showing that higher DER values tend to lower stock prices and reduce investor interest in those stocks.